Late Mesozoic to Cenozoic Tectonic Events in Volcanic Arc, West Burma Block： Evidences from U-Pb Zircon Dating and Apatite Fission Track Data of Granitoids - 李任远 梅廉夫 朱光辉 赵汝敏 许晓明 赵厚祥 张朋 尹宜鹏 马一行 (Journal of earth science (Wuhan, China), 2013)
Genetic type of basement granite from volcanic arc in the north of West Burma Block is S-type granites, which developed in volcanic arc of convergent plate margins. The results yield a group of weighted mean ^206pb/^238U ages at 102±0.81 Ma （MSWD=0.23）, which show similarity to 93.7±3.4 Ma in the northern part of sampling points and 105±2 Ma in the southern part of sampling points, indicating continuous development of volcanic arc in the north of West Burma Block and subsequent granitic intrusion of late Early Cretaceous. The apatite fission track age of the samples is 22.72±3 Ma, thermal history modeling reveals that the volcanic arc in the north of West Burma Block went through two main stages in the process of uplift-cooling since Cenozoic： rapid uplifting and cooling from Late Oligocene to Early Miocene （29±1 to 20±1 Ma） and slow uplifting and cooling since Early Pliocene （4.2±1 Ma）.